2017
DOI: 10.4236/jdm.2017.73017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between C-Reactive Protein, White Blood Cell Count and Metabolic Syndrome in Nigerians with Type 2 Diabetes Mellitus

Abstract: Background: Presence of metabolic syndrome (MS) in people with diabetes confers increased cardiovascular and diabetes-specific micro-and macrovascular complications. The pathogenic pathways for metabolic syndrome are still issues for discussion especially in some special groups like those with type 2 diabetes mellitus (T2DM). Recent evidences suggest that inflammation may play a key role in MS. This study assessed the relationship between MS (and its component risks) and markers of inflammation (high-sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…[6][7][8][9][10][15][16][17] One study result revealed no significant elevation of CRP in Mets patients. 18 Though there is some evidences of altered calcium, magnesium and CRP levels in MetS patients in separate studies of different countries in the world, there is no informed published data available in reproductive age group female in Bangladesh. Therefore, this study has been designed to assess serum calcium, magnesium and CRP status in a small cross section of female MetS patients in Bangladesh.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][15][16][17] One study result revealed no significant elevation of CRP in Mets patients. 18 Though there is some evidences of altered calcium, magnesium and CRP levels in MetS patients in separate studies of different countries in the world, there is no informed published data available in reproductive age group female in Bangladesh. Therefore, this study has been designed to assess serum calcium, magnesium and CRP status in a small cross section of female MetS patients in Bangladesh.…”
mentioning
confidence: 99%